Toward sustainable industrialization in Africa: the potential of additive manufacturing – an overview - Klenam, Desmond; Asumadu, Tabiri; Bodunrin, Michael; Obiko, Japheth; Genga, Rodney; Maape, Sechaba; McBagonluri, Fred; Soboyejo, Wole (Frontiers in Manufacturing Technology, 2025)
The integration of sustainable additive manufacturing (AM) within the framework of African industrialization presents a promising avenue for economic advancement while addressing environmental concerns. This review explores the convergence of sustainable AM practices with the industrial landscape of Africa, highlighting potential benefits and challenges. Through efficient resource utilization and localized production capabilities, AM holds promise for enhancing industrial resilience, stimulating employment opportunities, and fostering innovation. However, the realization of these benefits necessitates navigating infrastructural limitations, technological disparities, and regulatory complexities. By critically examining sustainable AM strategies and their relevance to African contexts, this review aims to delineate actionable pathways for leveraging the transformative potential of AM. The role of AM in industrialization as expressed in the African Union Agenda 2063 are highlighted. This has the potential to increase the staggering ∼11% contribution of manufacturing to gross domestic product of Africa. Collaboration through the triple helix approach focusing on government, industry and academia is highly pivotal for the success of such nascent and ubiquitous AM technology which is able to address the sustainable development goals. Africa can leapfrog and harness sustainable AM as a catalyst for inclusive industrial development and sustainable growth across the continent. The implications of AM for an industrialised Africa and areas for future research direction are briefly discussed.